A Review of the Development and Applicability of Double-Skin Facades in Hot Climates - Abtar, Aare N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
A double-skin façade (DSF) is a multilayered skin that was initially designed for the cold climate of European countries with noticeable success. Since then, countries in different climates started looking into the possibility of adopting DSF through the use of computer simulations to avoid any unforeseen problems in real life. This study aims to look into the possibility and level of success in using DSF in the Middle East’s hot-arid climate, making it a challenge compared to European countries. The study utilized a quantitative investigative approach in analyzing the results of some studies done in different countries in the Middle East. After looking into the results from different papers, careful considerations have to be made for the building due to its location and microclimate todetermine specific parameters (e.g., combination of transparent and opaque materials, proportion between floor level and screen height, orientation and cavity depth), these would lead to a significant impact on reducing a building’s cooling loads and energy efficiency. It is worth noting that mechanical ventilation (e.g., supplying all return cool air from internal spaces into the DSF cavity or integrating the building’s heating, ventilation, and air-conditioning system with the façade) is necessary for DSF in hot climates to cool and maintain its cavity’s temperature to function properly. However, this increases cooling loads, energy consumption, and running costs of the building which architects have to consider to determine the most efficient and economical solution in material and equipment.